INFLUENCE OF THE CHEMICAL COMPOSITION OF CHSHG ON THE STRUCTURE OF INGOTS AT CASTING BY DIRECTIONAL HARDENIN - E. I. Marukovich; V. Ju. Stezenko (Литьë и металлургия)
It is shown that Cr, Si and Сu influence mostly on the process of structure formation of castings at founding by directional hardening.